2015
DOI: 10.1177/1708538115597372
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm of an aberrant splenic artery: An extremely rare occurrence

Abstract: An aberrant splenic artery arising from the superior mesenteric artery, also known as the splenomesenteric trunk, is a rare anatomical variant seen in less than 1% of the population and is more common in females. Aneurysms of the splenic artery originating anomalously from the superior mesenteric artery are extremely rare; only 35 cases of aneurysm of an aberrant splenic artery have been described so far in the English medical literature. We report an extremely rare case of aneurysm of aberrant splenic artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Since the first case reported by Ghatan et al 7 in 1967, only 46 cases of an anomalous SAA have been reported. 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 A summary of the reported cases is shown in the Table . The mean diameter was 32.5 mm, and 63% of the patients were women.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first case reported by Ghatan et al 7 in 1967, only 46 cases of an anomalous SAA have been reported. 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 A summary of the reported cases is shown in the Table . The mean diameter was 32.5 mm, and 63% of the patients were women.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SA aneurysm is estimated to be around 0.8 %, though the exact number is not known [ 1 ]. We searched through the Medline, PubMed, and Google scholar and were able to find only 44 reported of anomalous SA aneurysms ( Table 1 ) [ 1 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. The combined rarity of these two conditions explains why so few cases are reported in English medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant splenic artery originating from SMT can also develop aneurysms close to its origin and aneurismal rupture leads to catastrophic consequences. Till date about 36 cases of aberrant splenic artery aneurysms have been reported and successfully treated in the English literature [26,27].…”
Section: Discussionmentioning
confidence: 99%